Efek Proteksi Vitamin E per Oral Terhadap Gangguan Memori Spacial Pada Tikus (Rattus norvegicus) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Dwi Cahyanr Ratna Sari, Soedjono Aswin, Kristy Iskandar - The protection effect of vitamin E administered orally on spatial memory of the rat (Rattus norvegicus/ Background: Various studies have shown that the antioxidant aliect of vitamin E provides its role as a neuroprotector. Vitamin E is distributed mainly in the hippocampus and other brain regions where the memory processes take place, objective: To reveal the protective effect of vitamin E on memory by measuring the latency (seconds'. to find platform of the rats In the watermaze. Methods: Three month male rats M=101 were divided randomly into 2 groups, Le. treatment group